1994
DOI: 10.3892/or_00000134
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated expression of spermidine/spermine N1-acetyltransferase gene induces S-phase arrest in human colorectal cancer cells

Abstract: Abstract. Spermidine/spermine N 1 -acetyltransferase (SSAT) is a key enzyme of polyamine catabolism. In a previous study, we constructed a recombinant adenovirus, Ad-SSAT, which can express human SSAT. In the present study, we investigated the effect of Ad-SSAT on the growth and cell cycle of colorectal cancer cells. We found that Ad-SSAT increased the expression of SSAT and inhibited the growth of HT-29 and LoVo cells. The growth inhibition was caused by cell cycle arrest in the S phase. Furthermore, Ad-SSAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Existing research (Du et al, 2022, Duxbury, Matros, et al, 2004 as gastric cancer, osteosarcoma, prostate cancer, liver cancer, and so on. The upregulation of E2F1 expression is closely associated with the occurrence, development, metastasis, and prognosis of tumors (Liang et al, 2016;Sun et al, 2008;Wang et al, 2017;Ye et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research (Du et al, 2022, Duxbury, Matros, et al, 2004 as gastric cancer, osteosarcoma, prostate cancer, liver cancer, and so on. The upregulation of E2F1 expression is closely associated with the occurrence, development, metastasis, and prognosis of tumors (Liang et al, 2016;Sun et al, 2008;Wang et al, 2017;Ye et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that E2F1 is greatly expressed in diverse tumors such as gastric cancer, osteosarcoma, prostate cancer, liver cancer, and so on. The upregulation of E2F1 expression is closely associated with the occurrence, development, metastasis, and prognosis of tumors (Liang et al, 2016; Sun et al, 2008; Wang et al, 2017; Ye et al, 2021). The above results suggest that silencing GGTase‐I is capable of inhibiting the modification of RhoA protein and thus affecting RhoA protein activity, rather than inhibiting RhoA protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…SSAT expressing recombinant adenovirus, Ad-SSAT was reported to cause a surge in the enzyme expression, where it limited the growth of HT-29 cells by arresting the cell cycle in S-phase. As seen from the reporter gene assay, Ad-SSAT suppressed the expression of nuclear factor E2F-1 and cyclin A in Lovo cells and HT-29 cells ( Sun et al, 2008a ).…”
Section: Spermidine/spermine N1-acetyltransferase (Ssat)-induced Anti...mentioning
confidence: 94%